Is small beautiful? Small Enterprise, aid and employment in Africa - John Page; Måns Söderbom (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Aid providers frequently link supporting small firms to job creation. Small firms create about half of new jobs in Africa, but they also have higher failure rates. Ignoring firm exit exaggerates net employment growth. Using panel data for Ethiopia, we find that small and large enterprises create similar numbers of net jobs. Moreover, wages in small firms are persistently lower. To create more good jobs aid should target the constraints to the growth of firms of all sizes. Improving the investment climate and new programmes to increase firms' capabilities - through for example management training - offer better prospects for employment creation.
Keywords: J23; O14; O17; O19; 330; aid; small enterprise; employment; firm exit; Africa